The utilization of the large unstained cell (LUC) parameter in lymphoid, haematopoietic and related tissue’s malignant neoplasms - Gök, Gamze; Erdoğan, Serpil; Asutay, Erbay; Yılmaz, Gülsen; Erel, Özcan; Yılmaz, Fatma Meriç (The European Research Journal, 2025)
Objectives: Large unstained cells (LUCs) are a differential count parameter reported by routine hematology analysis, and LUC percentages (LUC%) reflect active lymphocytes and peroxidase-negative cells. We aimed the evaluate the LUC% parameter in routine practice towards malignant neoplasms, stated or presumed to be primary, of lymphoid, haematopoietic, and related tissue. Methods: LUC analysis was performed with Siemens ADVIA® 2120 Hematology System. Data were obtained from Ankara Bilkent City Hospital’s laboratory information system. Results: A statistical difference in the LUC % data in the case of LUC % <4.5 and LUC % ≥4.5 among preliminary diagnoses was observed (P<0.001). According to the Kruskal-Wallis test, a statistical difference was observed between preliminary diagnosis and LUC % values (P<0.001). The One-way ANOVA test with Bonferroni correction was performed for post hoc multiple comparisons of the preliminary diagnosis among LUC%. LUC% was higher in Hodgkin Lymphoma patients than Myeloid leukaemia patients (P=0.002). LUC % was higher in the Lymphoid leukaemia patients than in the patients with Hodgkin lymphoma (P<0.001), Other and unspecified types of non-Hodgkin lymphoma (P<0.001), Multiple myeloma and malignant plasma cell neoplasms (P<0.001). LUC% was higher in patients with leukemia unspecified cell type than Hodgkin lymphoma (P<0.001), Follicular lymphoma (P<0.001), Non-follicular lymphoma (P<0.001), Mature T-Cell and Natural Killer Cell lymphomas (P<0.001), Other and unspecified types of non-Hodgkin lymphoma (P<0.001), Malignant immunoproliferative diseases (P<0.001), Multiple myeloma and malignant plasma cell neoplasms (P<0.001), Lymphoid leukaemia (P<0.001), Myeloid leukaemia (P<0.001), Other leukaemias of specified cell type patients (P<0.001). Conclusions: The present study underscores the importance of LUC% in line with ICD-10 and may provide ideas for new research. Prospective studies including patient and control groups may be useful in assessing LUC%.